2014
DOI: 10.1182/blood-2013-05-500595
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide copy-number analyses reveal genomic abnormalities involved in transformation of follicular lymphoma

Abstract: • Chromosome copy-number alterations that may affect immune surveillance and the NF-kB and p53 pathways are more frequent in tFL than FL.• Abnormalities involving chromosomes 6 and X are predictive of overall survival in FL.Follicular lymphoma (FL), the second most common type of non-Hodgkin lymphoma in the western world, is characterized by the t(14;18) translocation, which is present in up to 90% of cases. We studied 277 lymphoma samples (198 FL and 79 transformed FL [tFL]) using a single-nucleotide polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
122
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(147 citation statements)
references
References 56 publications
7
122
0
10
Order By: Relevance
“…Historically, TFL was considered to be related to the GCB subtype of de novo DLBCL, based on its transcriptional profile and the landscape of genetic alterations. 13,23 In keeping with the report by Bouska et al, 26 our study shows that a majority (80%) of TFL cases are of the GCB phenotype, but that a significant minority (16%) can nonetheless be identified as being of the ABC phenotype using the Lymph2Cx assay. In our series, ABC TFL cases did not have a poorer outcome after transformation than GCB TFL cases, although a definitive conclusion cannot be drawn due to the relatively small number of ABC cases and treatment heterogeneity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Historically, TFL was considered to be related to the GCB subtype of de novo DLBCL, based on its transcriptional profile and the landscape of genetic alterations. 13,23 In keeping with the report by Bouska et al, 26 our study shows that a majority (80%) of TFL cases are of the GCB phenotype, but that a significant minority (16%) can nonetheless be identified as being of the ABC phenotype using the Lymph2Cx assay. In our series, ABC TFL cases did not have a poorer outcome after transformation than GCB TFL cases, although a definitive conclusion cannot be drawn due to the relatively small number of ABC cases and treatment heterogeneity.…”
Section: Discussionsupporting
confidence: 91%
“…23 In the study reported by Bouska et al, 42 out of 59 (71%) TFL cases were reported to be of the GCB phenotype and 17 out of 59 cases (29%) of a non-GCB phenotype. 26 In addition, whereas assessment of translocations involving both the MYC and either the BCL2 or BCL6 genes ("double-hit lymphoma") allows for identification of a poor-risk category of de novo GCB-type DLBCL, [27][28][29] similar prognostic implications are less well studied in TFL. In this study, we sought to assess whether transformation can be predicted at the time of FL diagnosis using clinical annotation and information on histologic grade, fluorescence in situ hybridization (FISH) break-apart assays for recurrently rearranged genes (BCL2 and BCL6), and IHC for CD10, BCL6, and IRF4.…”
Section: Introductionmentioning
confidence: 99%
“…Gain of X is associated with inferior outcome in FL. [1][2][3][4] Analysis of 131 FL-samples in the LLMPP data set 10,17 confirmed these results (supplemental Figures 2-5). Using Ingenuity Systems Pathway Analysis, the molecular network most enriched for cis-genes was identified ( Figure 1C).…”
Section: Resultsmentioning
confidence: 55%
“…Most cases of transformed FL are classified as GCB subtype of DLBCL by gene expression profile or immunophenotype. 18 Using a high-resolution SNP array, copy number profiles of FL, and transformed FL showed similarities with the GCB, as well as the ABC subtype of DLBCL, 3,19 and genes involved in NFkB signaling were targeted by recurrent copy number aberrations. The predictive power of 6 NFkB target gene scores suggests that attainment of a more ABC-like phenotype predisposes FL for transformation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation